House Conditions Based on Public Knowledge of Healthy Homes in the Coastal Area of Wawonii Barat District, Konawe Islands Regency In 2022 - Tosepu, Ramadhan; ., Mirna; W.Yunita, Elda; Ratnawati, Lisdya; Insan, Nur; Sugiarti, Andi (KnE Social Sciences, 2023)
The purpose of this research was to review an overview of the condition of the house based on community knowledge about healthy homes in the coastal area of the West Wawonii sub-district, Konawe Regency, in 2022. The research design was descriptiveanalytic, with a cross-sectional approach where the independent variables (SPAL and TPS) and the dependent variables (healthy home conditions) are carried out only once and at the same time (Setiadi, 2007). The state of the houses in West Wawonii Sub-district, out of 2,302 homes found, only 1028 houses met the requirements, and 1,274 did not. There was a relationship between the level of understanding of PHBS and the house condition. There needs to be education treatment to improve PHBS in seeking simple healthy homes so even though the house did not meet the health requirements of the house occupants, it seeks components of sanitation facilities. Keywords: Understanding Level, House Condition, Healthy Home, Sanitation